Uncovering the Experiences of Engaging Indigenous Knowledges in Colonial Structures of Schooling and Research - McDermott, Mairi; MacDonald, Jennifer; Markides, Jennifer; Holden, Mike (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2021)
In response to the Truth and Reconciliation Calls to Action (TRC, 2015), a school board teamed with university educators and educational partners to generate a professional learning series to support educators’ engagement with Indigenous knowledges. A research team that assembled two years later interviewed the learning series participants to explore how educators were navigating Indigenous knowledge within a Eurocentric school system.  This research acknowledges the challenges of doing this work within shifting institutional policies and initiatives, the wider politics of Indigenous and non-Indigenous relations, building intercultural understandings and community partnerships, and negotiating epistemological difference. The researchers — including Indigenous and non-Indigenous peoples — echoed resonances with the participants that occurred throughout the data collection process and often spoke about the parallel paths of research and schooling — both historically used as tools of colonization and now having a role in decolonization. To disrupt colonial propensities, we share our reflections as researchers, specifically around complexities and tensions of engaging Indigenous knowledges throughout our research processes concerning the participants’ experiences. By sharing the tensions and (un)learning that emerged on these parallel paths, we honour diverse entry-points and experiences to animate how trans-systemic knowledge building might ensue.